Protein phosphatase 1, regulatory subunit 15B is a survival factor for ERα-positive breast cancer - Shahmoradgoli, Maria; Riazalhosseini, Yasser; Haag, Daniel; Becker, Natalia; Hovestadt, Volker; Heck, Stefanie; Sinn, Peter; Schneeweiss, Andreas; Mannherz, Otto; Şahin, Özgür; Lichter, Peter (International journal of cancer, 2013)
Breast cancer is a heterogeneous disease at both the clinical and molecular levels. This heterogeneity may give rise to different therapy responses. Molecular profiling has facilitated identification of signatures for stratifying patients who would potentially benefit from given therapies. Previously, we reported on a subset of genes with the potential for predicting response of primary breast cancer to neoadjuvant chemotherapy. Herein, we report that patients with luminal (estrogen receptor α [ERα]-expressing) breast cancer were enriched for nonresponders. To identify novel factors that contribute to the survival of breast cancer cells, a loss-of-function screen was performed with a subset of genes overexpressed in patients with disease resistant to chemotherapy. This approach led us to identify protein phosphatase 1, regulatory subunit 15B (PPP1R15B) as a factor with a potentially essential role in the survival of ERα-positive breast cancer cells. Functional analyses showed that PPP1R15B depletion results in impaired proliferation due to unsuccessful transition of cells from G1 to S phase of the cell cycle, and apoptosis induction. Moreover, our data revealed a regulatory role for PPP1R15B in activating ERα. Furthermore, a high level of PPP1R15B mRNA expression was associated with poor outcome following tamoxifen-based therapy. Accordingly, knockdown of PPP1R15B expression sensitized tamoxifen-resistant MCF-7 breast cancer cells to tamoxifen while reducing ERα abundance in these cells. Our findings reveal a novel role for PPP1R15B in the survival and therapy response of ERα-positive breast cancer and may open new avenues for tumor subtype-specific therapeutic strategies in the era of personalized medicine.
Online 20 Nov 2012
Gesehen am 19.08.2021